Fear as a barrier to physical activity in young adults with obesity: a qualitative study. Issue 1 (2nd January 2023) - Hamer, Oliver; Larkin, Derek; Relph, Nicola; Dey, Paola
ABSTRACT: Obesity continues to be a growing public health problem worldwide. In adults with obesity, physical activity has health benefits beyond those directly attributable to weight loss. However, adults with obesity encounter various barriers to physical activity. Some barriers including fear, have received little academic attention, particularly in adults under 45 years. The aim of this qualitative study was to explore how fears about physical activity are experienced by, and impact on, adults with obesity aged 18 to 45 years. Semi-structured interviews were undertaken in a sample of 10 participants with a body mass index greater than 30 kg/m 2 . Analysis was conducted using the six phases of thematic analysis from the guidelines of Braun and Clarke. Participants gave detailed accounts of their experiences of fear and how it impacted on physical activity. Three themes were extracted: (1) fear as a barrier to physical activity; (2) threats, concerns and worries about weight underpinning fear(s) of activity; and (3) the consequences of fear(s). The findings suggest that the emotion of fear, particularly pain-related fear(s), were a frequent and important barrier to physical activity among younger adults with obesity. This is an important finding because of the risk it poses to health behaviour change. The findings provide some evidence that younger adults experience fear avoidance beliefs aligned to the conceptual principles of the Fear Avoidance Model. Further research is needed to further explore this relationship in a larger sample of younger adults with obesity, and explore its implications for promoting behaviour change in this group.